Does Intergovernmental Transfers Cause Flypaper effect on Local Spending? - Agus Widarjono (Universitas Islam Indonesia, 2006)
The local expenditure in Indonesia either province level or district level rely upon intergovernmental transfers. Theoretically, if the lump sums transfers have more stimulate effect on the local expenditure rather than local private income, they can cause the flypaper effect phenomenon. This study investigates whether the intergovernmental transfer leads to the flypaper effect in the province level during 1995-2002. By using the panel data, the results demon-strate that intergovernmental transfers cause the flypaper effect. Our findings also show that the flypaper effect exists heavily at east region as a backward area than west region as a well-developed area. This finding supports the previous research in districts and municipali-ties.Keyword: Intergovernmental transfers, Local government, Flypaper Effect, panel data